KEANEKARAGAMAN DAN KELIMPAHAN ORTHOPTERA(INSECTA) DI GUNUNG KENDENG DAN GUNUNG BOTOL, TAMAN NASIONAL GUNUNG HALIMUN, JAWA BARAT, INDONESIA - Nety Virgo Erawati; Tri Atmowidi; Sih Kahono (BERITA BIOLOGI, 2004)
Study on diversity and abundance of Orthoptera (insect) was conducted at a tropical mountainous rainforest of Java, Mounts Kendeng and Botol, Gunung Halimun National Park, West Java, Indonesia, from January to March 2002. Total Orthoptera captured was 414 individuals,consist of 25 species and 9 families. Shannon Diversity Index and evenness were higher at Mount of Kendeng (2.44 and 0.81) rather than Mount Botol (1.80 and 0.66).Similarity Index of Jaccard and Sorenson of both localities were similar (0.40 and 0.32).Relative abundant of each family and species will be compared between the two locations also.